High expression of ECT2 and E2F1 is associated with worse clinical manifestations and prognosis in patients with oral squamous cell carcinoma. (20th October 2022) - Peng, Shixiong; Wang, Jinhang; Chen, Yanping; Hei, Naiheng; Zhao, Jianguang; Wu, Xinjuan; Cui, Zifeng
To detect the expression, prognostic value, and possible effects of epithelial cell transforming sequence 2 (ECT2) and E2F1 in patients with oral squamous cell carcinoma (OSCC). Seventy subjects hospitalized for OSCC surgical treatment in the Fourth Hospital of Hebei Medical University were selected for this study. Expression levels of ECT2 and E2F1 were detected by qRT-PCR, Western blot, and immunohistochemistry. The Kaplan-Meier method and Cox risk proportional regression analysis were used to analyze the relationship between different expression levels of ECT2 or E2F1 and the survival of patients with OSCC in 3 years. Relative expression levels of E2F1 mRNA (1.31 ± 0.15) and ECT2 mRNA (3.95 ± 0.72) in OSCC tissues, compared to adjacent normal tissues (0.87 ± 0.11, 1.03 ± 0.23, all p < 0.05). ECT2 was highly expressed in 42 (60.00%) OSCC samples and E2F1 was highly expressed in 45 (64.29%) samples. The expression of ECT2 and E2F1 was related to clinical stage, lymphatic metastasis, tumor differentiation grade, and tumor diameter in OSCC patients. The higher the expression of ECT2 and E2F1, the lower the 3-year survival rate of patients. ECT2 high expression (HR=2.407, p < 0.001), E2F1 high expression of E2F1 (HR = 2.159, p = 0.013), Clinical stages (III+IV) (HR = 1.362, p = 0.012), medium and low differentiation (HR = 1.522, p = 0.015), lymphatic metastasis (HR = 1.951, p < 0.001), and tumor diameter (≥3 cm) (HR = 1.824, p = 0.002) could be independent factors for 3-year survival of patients with OSCC. The expression of ECT2 and E2F1 in OSCC was significantly up-regulated, which was closely related to clinical stage, lymph node metastasis, tumor size, and 3-year survival of OSCC patients.